The Role of Energy Management Practices in Sustainable Tourism Development: A Case Study of Jerash, Jordan - Alhawamdeh, Hamzeh; Al-Saad, Saad A.; Almasarweh, Mohammad Salameh; Al-Hamad, Abd Al-Salam Ahmad; Bani Ahmad, Ahmad Y. A. Bani; Ayasrah, Firas Tayseer Mohammad (International Journal of Energy Economics and Policy, 2023)
This study investigates the mediating role of Top Management Commitment (TMC) on the relationship between Energy Management Practices (including Energy Awareness [EAW], Energy Efficiency [EE], and Energy Knowledge [EK]) and Sustainable Tourism Development (STD) in Jerash, Jordan. Amid growing global concerns about environmental sustainability, understanding the dynamics between energy management and sustainable tourism has become critically important. The study utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the collected data. The empirical results reveal that EAW, EE, and EK have a significant positive influence on STD, indicating the direct impact of energy management practices on the sustainability of tourism. Furthermore, the findings suggest that these energy management variables also significantly influence TMC. Intriguingly, TMC emerges as a substantial mediator, enhancing the positive effects of EAW, EE, and EK on STD. This signifies the crucial role of top management’s commitment to leveraging energy management practices effectively to foster sustainable tourism development. The study, despite focusing only on the context of Jerash, Jordan, contributes valuable insights to the existing literature and informs managerial practice in the tourism sector. Future research should expand its scope to different geographical regions and consider additional dimensions of energy management practices to further enrich the understanding of sustainable tourism development.